Indeks Keterbacaan Buku Aqidah Akhlak Kelas XI Di Madrasah Aliyah Kabupaten Bantul Yogyakarta - Muh. Isnanto (LP2M UIN Sunan Kalijaga, 2017)
The term readability index is essentially related to understandability in reading and its core is in the quality of the reader’s reading capacity, not the quality of the text. In this research index is connected to the term text readability, which is readability that is linked to text only i.e. a book and then linked to index. This research aims to describe the index of book readability, that is the level of cohesiveness between the core material and the entire book on Faith-Virtue of Grade XI Islamic Senior High School (MA) of the 2013 curriculum for Exact Science, Social Science, and Language interest classes which were organized by sub-chapters. The main point of this research is answering the question: what is the readability index/level of the book being analyzed, that is the level of appropriateness or cohesiveness of the core material with the entire content of the text book on Faith-Virtue for Grade XI MA from the 2013 curriculum for Exact Science, Social Science, and Language interest classes as organized by sub-chapters? And what are the response of the teachers regarding the substantive content of the book?Research results show that, firstly, the readability index of the Faith-Virtue Lesson is at 25%. The readability level of the analyzed book shows a level of appropriateness or cohesiveness between the core material with the entire content of the textbook on Faith-Virtue for Grade XI MA from the 2013 curriculum for Exact Science, Social Science, and Language interest classes. The value of readability index had a percentage of 82.3 (very high), with an average index acquired at 81.36, which shows that the readability index according to the readers at the Islamic Senior High School was very high. Secondly, regarding the quality of response according to the teachers, when comparing the K-13 (2013 curriculum) with the KTSP (Education Unit Level Curriculum), they thought that it was better when they were using the KTSP. The reason being the K-13 textbook seemed to be lacking in substantive depth. Hence an assembly for teachers of similar subject matter (MGMP) was held to compose a student work sheet (LKS) for this subject with the strongest reason, according to the teachers, being it is more practical and in-depth. Thirdly, there are discrepancies between the standard competence (KD) and the core material, there are inconsistencies of chapters – subchapters wherein the table of contents, technique in scientific writing, and book composition were not undertaken thoroughly and carefully. There were many notes acquired from the teachers’ reading results regarding corrections to complete the book.